English Teachers’ Purpose Applying Code Mixing In Classroom Interactions: A Sociolinguistic Study in Educational Context - Musmuliadi Musmuliadi (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research was aimed to find out the forms and purpose of code mixing applied by the English teacher in In Classroom Interactions. This study is descriptive qualitative method in which the data are conversation that has done by the English teacher in teaching and learning process. There are two instruments is used to get data namely recorder and structured interview. Meanwhile techniques of data collection are recording and interview. Data analysis involved three steps, those are data reduction, data display and conclusion drawing/verification. The result of this study found, 45 forms of word 19 forms of phrase 9 form of hybrid 2 forms of word repetition and 11 forms of clause. Meanwhile, the researcher found 3 purposes of using code mixing those are need feeling motive, more being informative and expressing self-emotion.